Unique heterologous fibrin biopolymer with hemostatic, adhesive, sealant, scaffold and drug delivery properties: A systematic review - Buchaim, Daniela Vieira; Cassaro, Claudia Vilalva [UNESP]; Shindo, João Vitor Tadashi Cosin; Coletta, Bruna Botteon Della; Pomini, Karina Torres; De Oliveira Rosso, Marcelie Priscila; Campos, Leila Maria Guissoni; Ferreira, Rui Seabra [UNESP]; Barraviera, Benedito [UNESP]; Buchaim, Rogério Leone (FapUNIFESP (SciELO), 2019)
Fibrin biopolymers, previously referred as fibrin glue or fibrin sealants, are natural biomaterials with diverse applications on health. They have hemostatic, adhesive, sealant, scaffold and drug delivery properties and have become widely used in medical and dental procedures. Historically, these biomaterials are produced from human fibrinogen and human or animal thrombin, and the possibility of transmission of infectious diseases by human blood is not ruled out. In the 1990s, to overcome this problem, a new heterologous biomaterial composed of a thrombin-like enzyme purified from Crotalus durissus terrificus venom and a cryoprecipitate rich in fibrinogen extracted from buffaloes Bubalus bubalis blood has been proposed. Therefore, a systematic review of studies on exclusively heterologous fibrin sealants published between 1989 and 2018 was carried out using the following databases: PubMed, SciELO and Google Scholar. The keyword used was heterologous fibrin sealant. The search resulted in 35 scientific papers in PubMed, four in SciELO and 674 in Google Scholar. After applying the inclusion/exclusion criteria and complete reading of the articles, 30 studies were selected, which formed the basis of this systematic review. It has been observed that the only completely heterologous sealant is the one produced by CEVAP/UNESP. This heterologous biopolymer is proven effective by several studies published in refereed scientific journals. In addition, clinical trials phase I/II for the treatment of chronic venous ulcers authorized by the Brazilian Health Regulatory Agency (ANVISA) were completed. Preliminary results have indicated a safe and promising effective product. Phase III clinical trials will be proposed and required to validate these preliminary findings.
Keywords: Cryoprecipitate coagulum; Fibrin sealant; Snake venom; Thrombin-like enzyme